PEDAGOGLARNING KASBIY EHTIYOJLARINI ANIQLASH MALAKASINI OSHIRISH HAMDA TAKOMILLASHTIRISH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The quality of education in every age and place has determined the development of the country in social, economic, political, legal and other spheres. This is an important issue for our independent Uzbekistan. Given that the quality of education is directly related to educators, it is important to study, identify, address existing problems, and address the most important issues of their qualifications, experience, skills, knowledge and competencies. should feel that.